Perioperative management of patients on new oral anticoagulants. Issue 7 (29th April 2014) - Lai, A.; Davidson, N.; Galloway, S. W.; Thachil, J.
<x xml:space="preserve">Abstract</x> Background New oral anticoagulants (NOACs) offer an alternative to warfarin for preventing stroke in patients with atrial fibrillation. NOACs are expected to replace warfarin and other vitamin K antagonists for most of their indications in the future. Knowledge of the use of NOACs in the perioperative period is important for optimal care. Methods Studies that reported on the use of NOACs were identified, focusing on evidence‐based guidance relating to the perioperative period. PubMed was searched for relevant articles published between January 2000 and January 2014. Results The anticipated expanded clinical use of NOACs such as rivaroxaban (Xarelto™), apixaban (Eliquis™) and dabigatran (Pradaxa™) has the potential to simplify perioperative anticoagulant management because of fewer drug–drug interactions, rapid onset of action, predictable pharmacokinetics and relatively short half‐lives. However, coagulation status cannot be monitored by international normalized ratio and no antidotes are currently available. In elective surgery, it is important to discontinue the use of NOACs, with special consideration of renal function as route of elimination. Guidelines for the management of bleeding complications in patients on NOACs are provided, and may be considered for trauma and emergency surgery. Haemodialysis could be considered for bleeding with use of dabigatran. Better options for reversal of the effects of NOACs when bleeding occurs may follow with novel drugs. Conclusion Management of NOACs in elective and emergency conditions requires knowledge of time of last intake of drug, current renal function and the planned procedure in order to assess the overall risk of bleeding. Currently no antidote exists to reverse the effects of these drugs.